Design Voltage Controller of Bipolar SPWM Voltage Source Inverter - Irna Tri Yuniahastuti; Senoaji (Journal of Advanced Technology and Multidiscipline, 2022)
This paper presents single phased VSI (Voltage Source Inverter) type bipolar SPWM. The main purpose of this system is generating a constant sinusoidal output waveform without affected by load (resistive) demand. Its concept is to get reference voltage from PI control and compare it with modulated triangular carrier for controlling inverter’s switches. The system is also represented by a LCL output ﬁlter. The LCL ﬁlter is employed to reduce the high frequency harmonic components in current waveform due to PWM switching and to reduce the output current THD. Simulation result and analysis are bravely presented to verify the effectiveness of proposed approach.